Indian Chiefs - Freedman, Russell (New York Holiday House, 1987)
Biographies of six Western Indian chiefs who led their people in a historic moment of crisis, when a decision had to be made about fighting or cooperating with the white pioneers encroaching on their grounds.
Includes bibliographical references (p. 143-144) and index.
Keywords: Indians of North America -- Biography -- Kings and rulers; Indians of North America -- Biography; Kings, queens, rulers, etc